Sodium tanshinone IIA sulphate inhibits angiogenesis in lung adenocarcinoma via mediation of miR-874/eEF-2K/TG2 axis - Bu Wang; Fang Zou; Gu Xin; Bao-Li Xiang; Jian-Qing Zhao; Sheng-Fang Yuan; Xiu-Long Zhang; Zhi-Hua Zhang (Taylor & Francis Group, 2023)
AbstractContext Sodium tanshinone IIA sulphate (STS) is a product originated from Salvia miltiorrhiza Bunge [Lamiaceae], which exerts an antitumour effect. However, the role of STS on lung adenocarcinoma (LUAD) remains unexplored.Objective Our study explores the effect and mechanism of STS against LUAD.Materials and methods LUAD cells were treated with 100 μM STS for 24 h and control group cells were cultured under normal medium conditions. Functionally, the viability, migration, invasion and angiogenesis of LUAD cells were examined by MTT, wound healing, transwell and tube formation assay, respectively. Moreover, cells were transvected with different transfection plasmids. Dual luciferase reporter and RNA immunoprecipitation (RIP) assays were used to verify the relationship between miR-874 and eEF-2K.Results STS significantly decreased the viability (40-50% reduction), migration (migration rate of A549 cells from 0.67 to 0.28, H1299 cells from 0.71 to 0.41), invasion (invasion numbers of A549 cells from 172 to 55, H1299 cells from 188 to 35) and angiogenesis (80-90% reduction) of LUAD cells. Downregulation of miR-874 partially abolished the antitumour effect of STS. EEF-2K was identified to be the target of miR-874, and its downregulation markedly abolished the effects of miR-874 downregulation on tumourigenesis of LUAD. Moreover, silencing of TG2 abrogated eEF-2K-induced progression of LUAD.Discussion and Conclusions STS attenuated the tumourigenesis of LUAD through the mediation of the miR-874/eEF-2K/TG2 axis. STS is a promising drug to fight against lung cancer, which might effectively reverse drug resistance when combined with classical anticancer drugs.